Natural sources, refined extraction, biosynthesis, metabolism, and bioactivities of dietary polymethoxyflavones (PMFs) - Renyou Gan; Yi Liu; Hang Li; Yu Xia; Huan Guo; Fang Geng; Qiguo Zhuang; Huabin Li; Dingtao Wu (Food Science and Human Wellness)
Polymethoxyflavones (PMFs) are a type of uncommon dietary flavonoids, characterized by more than one methoxy group, which exist in limited plant species, like Citrus species and Kaempferia parviflora. In addition, different PMFs, such as nobiletin, sinensetin, tangeretin, and casticin, have been isolated from these natural sources. PMFs have received increasing attention due to their multiple bioactivities, such as antioxidant, anti-inflammatory, anti-cancer, metabolic regulatory, immunoregulatory, neuroprotective, and skin protective effects. These bioactivities of PMFs should be associated with the regulation of critical molecular targets and the interaction with gut microbiota. In order to provide a comprehensive and updated review of PMFs, their natural sources, refined extraction, biosynthesis, metabolism, and bioactivities are summarised and discussed, with the emphasis on the molecular mechanisms of PMFs on regulating different chronic diseases. Overall, PMFs may be promising flavonoids to the forefront of nutraceuticals for the prevention and/or treatment of certain human chronic diseases.